Extracellular polymeric substances with metal adsorption capacity produced by Pseudoalteromonas sp. MER144 from Antarctic seawater - Caruso, Consolazione; Rizzo, Carmen; Mangano, Santina; Poli, Annarita; Di Donato, Paola; Nicolaus, Barbara; Di Marco, Gaetano; Michaud, Luigi; Lo Giudice, Angelina (Environmental Science and Pollution Research, 2018)
The EPS-producing Pseudoalteromonas sp. MER144 was selected among 606 isolates from Antarctic seawater due to its evident slimy appearance on agar plates. The production of EPSs was enhanced by a step-by-step approach varying the carbon source, substrate and NaCl concentrations, temperature, and pH. Optimal conditions for the EPS production resulted at temperature of 4 Â°C and pH 7, with addition of 2% sucrose (w/v) and 3% NaCl (w/v). EPSs produced under optimal conditions were chemically characterized, resulting in a moderate carbohydrate content (35%), uronic acids (14%), and proteins (12%). Monosaccharide composition was estimated to be Glu:Man:GluN:Ara:GluA:GalA:Gal (1:0.36:0.26:0.06:0.06:0.05:0.03), while the estimated molecular weight was about 250 kDa. The addition of sucrose in the culture medium, by stimulating the EPS production, allowed MER144 to tolerate higher concentrations of mercury and cadmium. This finding was probably dependent on the presence of uronic acids and sulfate groups, which can bind cations, in the extracted EPSs. Monitoring EPS production under optimal conditions at different concentrations of mercury and cadmium revealed that EPS amounts increased at increasing heavy metal concentrations, indicating an adaptation to the stress conditions tested.